PERAN HARGA, LOKASI, DAN ONLINE CUSTOMER REVIEW DALAM MEMENGARUHI KEPUTUSAN PEMBELIAN DAGHAN COTTAGE - Araeza, I Dewa Gede Revindra; Prawitasari, Putu Putri (Jurnal Bina Bangsa Ekonomika, 2025)
Along with the increasing number of hotels that have sprung up in Nusa Penida, the level of competition between them is getting hotter. When it comes to hospitality, the competition is not only fierce in terms of promotions and physical amenities such as rooms, but also price and location, two factors that play a crucial role in a customer's decision to stay or not. The research team at Daghan Cottage Hotel sought to measure the impact of three factors on online bookings: price, location, and customer reviews. No specific number of domestic clients who had booked hotel rooms at Daghan Cottage were included in the population of this study. A total of 113 samples were used for data processing, with a minimum of 102 samples actually identified. A quantitative strategy based on multiple linear regression is used for this investigation. Based on the findings of this study, the online booking platform at Daghan Cottage Hotel is somewhat influenced by prices, location, and online customer reviews